Pola Penggunaan Internet Mahasiswa Desain sebagai Sumber Inspirasi pada Tahap Awal Desain (Early Phase Design) - Muhammad Hajid An Nur (Institut Seni Indonesia Yogyakarta, 2019)
AbstractThis study aims to determine the pattern of internet use as a source of inspiration for design students in the early stages of the design process. In the design process, words and images are factors that greatly influence creativity, and the internet makes it easy for students to access these data. The research conducted through distributing questionnaires to undergraduate product design students to determine their internet usage tendency in finding design inspiration. By knowing the pattern of internet usage and what sites they usually visit, we can find out the input quality that students get independently when looking for inspiration. This is an important aspect to avoid design fixation.The result shows that in the process of searching for inspiration through the internet, students tend to use sites that are general and have more visual data (such as pinterest) in the first place, then followed by searching more about linguistic data (design explanations, features, functions, etc.) (such as behance), and then the usage tend to be more diverse depending on each students style and preference. The use of search keywords is still dominated by references that are near and even exactly the same as the design categories they are developing (exp. searching car designs reference when designing cars). This enhances the possibility of design fixation.To enhance the quality of input obtained by students will be better and reduce the possibility of design fixation, higher education institution could make the finding inspiration process in a more structured system such as lectures or other formal method. Key words: product design, early phase design, internet, creativity, design education